Análise do desenvolvimento de crianças de escolas privadas de educação infantil - Nicoletti, Lívia (Universidade Federal de São Carlos, 2025)
Given the importance of assessing child development, the objective of this study was to analyze the development of early childhood education children using the Operationalized Portage Inventory. Fourteen children aged 4 to 5 participated in the study: six girls, one with ASD, and eight boys, from two private schools in a city in the interior of São Paulo. The inclusion criteria for this study were: (a) students aged 4 to 5; (b) students attending school who agreed to participate; and (c) parents/guardians authorized their participation. After approval by the Research Ethics Committee and the board of directors responsible for the private schools, parents/guardians of students who met the study criteria were invited and informed about the research objective and how data collection would occur. After consenting to participate by signing the Informed Consent Form, the Family Environment Resource Inventory was provided to better understand these children's routines, including their use of free time, outings, shared activities with their parents at home, toys and books, and other information. The parent/guardian was also asked to answer the following questions: date of birth; how long the child has been attending school; extracurricular activities/professional services received by the child; any diagnosis; and birth (preterm, full-term, or post-term). The children's development assessment sessions took place in the classroom. The researcher observed and recorded the children's behaviors, considering the five developmental areas of the Operationalized Portage Inventory (motor development, cognition, language, socialization, and self-care). After data collection, a report on the child's performance was provided to the parent/guardian. The results showed that three participants performed above the expected level for their age group in all areas of development assessed; nine participants performed within the expected range for their age group in the areas of motor development, cognition, language, socialization, and self-care difficulties. Two participants, one with ASD, performed below the expected range for their age group in all areas assessed. Overall, the data analyzed demonstrate how the opportunities offered to children directly impact their overall development and how family interaction contributes to development.
Analysis of the development of children in private early childhood education schools
Keywords: Desenvolvimento infantil; Educação infantil; Pré-escolar; Child development; Early childhood education; Preschool; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO